Efficacy of bio-rational insecticides against major rice pests under field conditions in South Sulawesi, Indonesia - Jumardi; Desriani; Muh Sandy; Erwin Erwin; Nurasiah Djaenuddin; Andi Nasruddin (Universitas Lampung, 2026)
The brown planthopper (Nilaparvata lugens), green leafhopper (Nephotettix virescens), and yellow stem borer (Scirpophaga incertulas) are among the most destructive insect pests of rice in Indonesia. This study evaluated the field performance of four biorational insecticides (abamectin, azadirachtin, Beauveria bassiana, and Metarhizium anisopliae) and two synthetic insecticides (carbofuran and demihipo) in a rice field in Belawa, Wajo Regency, South Sulawesi, Indonesia. The experiment was arranged in a split-plot randomized complete block design. All biorational insecticides significantly reduced pest populations compared with the untreated control. Abamectin provided the greatest suppression of N. lugens (84.1%), whereas abamectin, carbofuran, and demihipo were the most effective treatments against N. virescens, reducing populations by 71.8%, 69.2%, and 82.4%, respectively. Against S. incertulas, azadirachtin and abamectin achieved the highest reduction in dead-heart incidence (91.9% and 85.7%, respectively). Predator populations, particularly Coccinella spp., were largely conserved in plots treated with azadirachtin, B. bassiana, and M. anisopliae, indicating good compatibility with beneficial arthropods. Weekly applications provided pest suppression comparable to twice-weekly applications, suggesting that insecticide inputs can be reduced without compromising efficacy. Overall, the findings demonstrate that biorational insecticides can be effectively integrated into rice IPM programs to suppress major pests, conserve beneficial arthropods, and reduce reliance on conventional synthetic insecticides, thereby supporting more sustainable rice production.